Suppression of fructose‐bisphosphate aldolase C expression as a predictor of advanced oral squamous cell carcinoma. (13th November 2015) - Li, Yue‐Ju; Huang, Tse‐Hung; Hsiao, Michael; Lin, Been‐Ren; Cheng, Shih‐Jung; Yang, Cheng‐Ning; Lai, Wei‐Ting; Wu, Tai‐Sheng; Fan, Jia‐Ruei; Kuo, Mark Yen‐Ping; Chang, Cheng‐Chi
Abstract: Background: Glycolysis machinery regulates cancer cell behavior. However, the roles of these glycolysis enzymes in oral squamous cell carcinoma (OSCC) progression remain unknown. Methods: Fructose‐bisphosphate aldolase C (ALDOC) expression in OSCC patients and cell lines was detected using quantitative real‐time polymerase chain reaction (PCR). The functions of ALDOC in migration and invasion were determined using gain and loss of function approaches. An orthotopic OSCC animal model was performed to investigate the effects of ALDOC on metastasis and tumorigenesis in vivo. Results: ALDOC expression is negatively significantly correlated with clinical outcome and cell migration in vitro and in vivo. ALDOC blocks adenosine triphosphate generation and lactate production, and mutation constructs of Arg42 and Lys146 functionally restore ALDOC‐inhibited cell migration and invasion. Conclusion: ALDOC functions as an OSCC prognosis marker clinically, and suppresses migration and invasion by its catalytic domain of Arg42 and Lys146. © 2015 Wiley Periodicals, Inc. Head Neck 38 : E1075–E1085, 2016